Mulan [videorecording] - Cook, Barry, direction; Bancroft, Tony, direction; Coats, Pam ([Burbank, Ca.] : Walt Disney Pictures, 2004)
A spirited young girl named Mulan, who doesn't quite fit into her tradition-bound society, discovers that her aging father has been ordered to help defend China against the invading huns. In a brave and selfless act, Mulan disguises herself as a man and takes his place in the Imperial Army, training with a comical group of warriors, led by the handsome Captain Shang. Never far away are Mulan's hilarious guardian dragon, Mushu, and lucky cricket, Cri-Kee. But Mulan will need more than Mushu's razor-sharp wit to defeat the ruthless Hun leader, Shan-Yu. Only by staying true to her heart will Mulan blossom into a skilled soldier and bring victory to her nation and long-awaited honor to her family.
Title from title screen
Screenplay, Rita Hsiao ; music, Matthew Wilder ; lyrics, David Zippel ; original score, Jerry Goldsmith
VCD format
Keywords: Hua, Mulan (Legendary character) -- Drama; Man-woman relationships -- Drama; Animated films; Historical films